PENGARUH PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA SD - Santa, Yustina Novia; Kartono, Kartono; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to examine the presence or absence of influence and the influence of the use of learning contextual teaching and learning to the learning outcomes of Natural Sciences in the fourth grade students of Elementary School Negeri Gugus I Pontianak Selatan. The research method used is experimental with quasi experimental design and nonquivalent control group design. The sample of this research is students of class IV B and IV C State Elementary School 35 South Pontianak. Data collection techniques used are measurement techniques. Data collection tool used is the test of student learning outcomes in the form of multiple choice amounted to 40 questions. Based on the result of the research, the average of students 'learning outcomes in the control class is 69 while the average of the students' learning outcomes in the experimental class is 76,5. The result of hypothesis test (t-test) using t-test separated variance obtained tcount of 4.54 and ttable (? = 5% and dk = 67) equal to 1.6695 indicates that tcount is greater than ttable then Ha is accepted. This means that there are differences in learning outcomes between students taught by using learning contextual teaching and learning with students taught without using learning contextual teaching and learning. From the calculation of effect size (ES), obtained 0.77 (medium criterion). Learning contextual teaching and learning gives a moderate influence on the result of learning of Natural Sciences on the fourth grade students of Elementary School of State I of Pontianak Selatan. Keywords: contextual teaching and learning learning, learning outcomes, natural sciences.